Motivasi Berprestasi, Berafiliasi, dan Kekuasaan dalam Persfektif Gender - Wiswanatha Mada, I Gede Nyoman Carlos; Mujiati, Ni Wayan (E-Jurnal Manajemen, 2014)
The aim of this study was to determine the condition of achievement motivation, affiliation and power in gender perspective in PT. Bangun Bali Utama. In addition, to determine whether there is any difference in achievement motivation, affiliation, and power in a gender perspective, as well as to find out the differences among the three greatest motivation in a gender perspective. The analysis technique used is Descriptive Statistics, Average Difference Testing Two Samples. The analysis showed the condition of achievement motivation, affiliation, and power in a gender perspective, most of the motivation of men is higher than women. Motivation ruling has the largest difference from the third motivation. Advice can be given as a material consideration in the PT. Bangun Bali Utama is more concerned employees to be able to accept a relatively high risk, able to solve problems in the workplace, it can create a strong relationship between employees and leaders to be more attention to employees who have a suitable character as leaders in their respective fields so as to increase motivation their work. Keywords: Achievement Motivation, Motivation Affiliated, Motivation Power and Gender